Evaluation of Patient Reported Safety and Efficacy of Cannabis From a Survey of Medical Cannabis Patients in Canada - Cahill, Shaina P.; Lunn, Stephanie E.; Diaz, Patrick; Page, Jonathan E. (Frontiers in Public Health, 2021)
With the medical use of cannabis permitted in Canada since 2001, patients seek to use this botanical drug to treat a range of medical conditions. However, many healthcare practitioners express the need for further scientific evidence around the use of medical cannabis. This real-world evidence study aimed to address the paucity of scientific data by surveying newly registered medical cannabis patients, before beginning medical cannabis treatment, and at one follow up six weeks after beginning medical cannabis treatment. The goal was to collect data on efficacy, safety and cannabis product type information to capture the potential impact medical cannabis had on patient-reported quality of life (QOL) and several medical conditions over a 6-week period using validated questionnaires. The 214 participants were mainly male (58%) and 57% of the population was older than 50. The most frequently reported medical conditions were recurrent pain, post-traumatic stress disorder (PTSD), anxiety, sleep disorders [including restless leg syndrome (RLS)], and arthritis and other rheumatic disorders. Here we report that over 60% of our medical cannabis cohort self-reported improvements in their medical conditions. With the use of validated surveys, we found significant improvements in recurrent pain, PTSD, and sleep disorders after six weeks of medical cannabis treatment. Our findings from patients who reported arthritis and other rheumatic disorders are complex, showing improvements in pain and global activity sub-scores, but not overall changes in validated survey scores. We also report that patients who stated anxiety as their main medical condition did not experience significant changes in their anxiety after six weeks of cannabis treatment, though there were QOL improvements. While these results show that patients find cannabis treatment effective for a broad range of medical conditions, cannabis was not a remedy for all the conditions investigated. Thus, there is a need for future clinical research to support the findings we have reported. Additionally, while real-world evidence has not historically been utilized by regulatory bodies, we suggest changes in public policy surrounding cannabis should occur to reflect patient reported efficacy of cannabis from real-world studies due to the uniqueness of medical cannabis’s path to legalization.